Studies on mononuclear chelates derived from substituted Schiff base ligands: Synthesis and characterization of a new 5-methoxysalicyliden-p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II), and Zn(II) - Canpolat, E; Kaya, M (Pleiades Publishing Ltd, 2005)
New complexes of Co(II), Ni(II), Cu(II), and Zn(II) with new Schiff bases derived by the condensation of p-aminoacetophenoncoxime with 5-methoxysalicylaldehyde are synthesized. The compounds are characterized by elemental analyses, magnetic susceptibility measurements, IR, H-1 and C-13 NMR spectra, elec, ironic spectral data, and molar conductivity. The thermal stabilities of the compounds are also reported. The Schiff base acts as bidentate O,N-donor atoms, and their metal complexes are supposed to possess a tetrahedral geometry with respect to the central metal ion. The general formula of the 5-methoxysalicyliden-p-aminoacetophenoneoxime Co(II), Ni(II), Cu(II), and Zn(II) complexes is Co(L)(2), Ni(L)(2), Cu(L)(2), and Zn(L)(2).
Keywords: Metal-Complexes; Spectral Characterization; Infrared-Spectra; Copper(Ii); Nickel(Ii); Cobalt(Ii); Zinc(Ii)